A Comparative exploration of podcasted code-switching and code-mixing utterances: A study case Deddy Corbuzier and Cinta Laura - Wardana, I Ketut (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
The surge in research addressing code-switching (CS) and code-mixing (CM) occurrences between English and Indonesian languages within podcasts has garnered significant attention.. Nonetheless, the comparative analysis of the structure, categories, and purpose of employing these linguistic blends, along with the audience's interpretations of such bilingual variations, remains somewhat limited. Consequently, the present study endeavors to contrast the distinct manifestations of CS and CM exhibited by Deddy Corbuzier and Cinta Laura, as perceived by participants. The study employed a qualitative approach where the data was analyzed with content analysis. Concurrently, participants' viewpoints regarding CS and CM were elicited through questionnaires distributed among a purposive sample of 20 individuals selected from a population of 200. The data were analyzed using a paired sample t-test. The findings of this research indicate Cinta Laura employed a greater degree of CS and CM in comparison to Deddy Corbuzier in the podcasts due to her fluency in both languages and her speech mostly indicated her social status and addressed topics of conversation. Meanwhile, Dedy Corbuzier used the variation to demonstrate solidarity and persuade the audience. The paired sample t-test revealed a significant divergence in participants' perceptions of code-switching and code-mixing between Deddy Corbuzier and Cinta Laura.